Pengaruh Aplikasi Dapodik Dan Tunjangan Profesi Guru Terhadap Kinerja Pendidik Sekolah Menengah Pertama (SMP) Di Kabupaten Tulungagung - Yuwitoro, Rano; Rusandy, Debby Satyo (Otonomi, 2024)
This research aims to: Analyzing the simultaneous significant influence of the Dapodik aplication and the teacher professional allowance and aducators performance ; analyzing the impact of the Dapodik aplication on educators performance ; analyzing the impact of the teacher professional allowence on aducators performance and determining the dominant influence betwen the Dapodik plication and profesional allowence on aducators performance ;This research uses Descriptive Quantitative. the population in this research is in the population consict of middle school (SMP) educators in Tulungagung regency totaly 450 individuals. The research sample comprises 10% of the population,, wich is 45 individulas The technique is a method of data collection now. In this study, researchers used the software (software), Microsoft Office Excel 2007 to carry out a descriptive and statistical analysis software (software) Statistical Package for Social Sciences (SPSS) for Windows version 21.0 to carry out the test, test the classical, hypothesis testing and multiple linear regression analysis, , The research findings indicate a significant dapodic application and teacher proffecional allowence on educators performance, meanwhile the most dominant influencingvariable is the teacher proffecionals allowence